Hubungan Pelayanan Dan Komunikasi Perawat Dengan Kepuasan Pasien - Dwi Puja, Okta; Aprina, Aprina; Sunarsih, Sunarsih (Poltekkes Kemenkes Tanjung Karang, 2024)
Proper and standard healthcare services will provide patient satisfaction in evaluating healthcare performance. Based on interviews conducted in December 2023 in the Surgical Inpatient Room at RSUD DR. H. Abdul Moeloek, Lampung Province, with 10 respondents, 6 respondents (60%) they were stated that some nurses did not explain the actions to be taken and were slow to respond to patient complaints. This study aims to determine the relationship between nurse services and communication with patient satisfaction in the surgical inpatient room of RSUD Dr. H. Abdul Moeloek, Lampung Province. This study was conducted in March-April using a quantitative method with a descriptive-analytic design through a cross-sectional approach. The study population was 83 respondents selected through accidental sampling (accidental sampling, also known as convenience sampling, is often considered a weak sampling technique because it does not ensure that the sample is representative of the larger population). Data collection instruments used questionnaires with dependent variables of patient satisfaction and independent variables of nurse services and communication. Data analysis used the Chi-square test. The results showed that 94% (78) of respondents stated that nurse communication was always good, and 96.4% (80) stated that nurse services were good. The correlation results showed a p-value=0.000<0.050, indicating a significant relationship between nurse services and communication with patient satisfaction. It is recommended that nurses continue to provide good, prompt, friendly, and always smiling services to patients.